An investigation on perceived relationship between motivation and interaction of second language’s learners - Abd. Aziz, Marzilah; Nordin @ Baharuddin, Mohd. Khairi (2010)
This study attempts to investigate the correlation between two types of motivation; these are intrinsic and extrinsic motivation, and interaction among Universiti Teknologi Malaysia students participating in the Friends of English (FoE) program. 65 participants of the Foe program participated in this research. The descriptive study was carried out in form of survey by using questionnaires with some questions adapted from Intrinsic Motivation Inventory (IMI): The Post-Experimental Intrinsic Motivation Inventory by Ryan (1982). The data gained through the survey were processed using SPSS software and results were interpreted based on the Guilford benchmark table. The results are presented in form of graphs and tables. The finding from this survey had revealed that there are significant relations between motivation and interaction. The strong relation between intrinsic motivation and interaction shows that students value FoE and find the program useful. The strong relation between extrinsic motivation and interaction shows that students value FoE and find the program useful. However, between the two types of motivation, extrinsic motivation shows higher relation suggesting that extrinsic motivation has stronger impact towards interaction than intrinsic motivation. However, there are several other things also affecting the findings. As for that, several recommendations to improve the students’ interaction using English have been made.